Complete transverse vaginal septum complicated by pyocolpos, primary vesicoureteral reflux and ectopic ureter with renal loss: a case report - Izadora Gabriela Coutinho; Paulo Acácio Egger; Ailton Fernandes Junior; Angelo Cezar Bolognese Junior; Abikeilla Ariane Bomfim Gomes Bernardi; Amanda Yumi Ono Valderrama (Urology Case Reports)
A transverse vaginal septum is a rare Müllerian anomaly caused by incomplete fusion between the Müllerian ducts and the urogenital sinus. It can obstruct menstrual flow, leading to hematocolpos, hydrocolpos, or pyocolpos. We report a 12-year-old girl with recurrent hematocolpos, abdominal pain, urinary symptoms, and infections. Imaging showed a complete transverse vaginal septum and grade II vesicoureteral reflux. She underwent surgical drainage, septum resection, and ureteral reimplantation. Recovery was favorable, with symptom resolution and preserved renal function. This case emphasizes the need for early diagnosis and a multidisciplinary approach to avoid long-term complications in complex urogenital anomalies.